2024
DOI: 10.1021/envhealth.3c00174
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Evaluation of Microplastics Thresholds to Inform Water Treatment Needs and Risks

Omar S. Chowdhury,
Philip J. Schmidt,
William B. Anderson
et al.

Abstract: Although human health impacts of microplastics are not well understood, concern regarding chemical contaminants retained on or within them is growing. Drinking water providers are increasingly asked about these risks, but strategies for evaluating them and the extent of treatment needed to manage them are currently lacking. Microplastics can potentially induce health effects if the concentration of contaminants adsorbed to them exceeds predetermined drinking water guidelines (e.g., Maximum Contaminant Levels).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The recovery of labeled MPs in replicate samples has also been found to be nonconstant, leading to further uncertainty in concentration estimates. Therefore, understanding the intrinsic errors associated with the analytical procedure and quantifying the uncertainty in MP concentration estimates arising from these errors are crucial for enhancing the accuracy and reliability of MP enumeration in wastewater and sludge samples as well as simpler sample matrices …”
Section: Introductionmentioning
confidence: 99%
“…The recovery of labeled MPs in replicate samples has also been found to be nonconstant, leading to further uncertainty in concentration estimates. Therefore, understanding the intrinsic errors associated with the analytical procedure and quantifying the uncertainty in MP concentration estimates arising from these errors are crucial for enhancing the accuracy and reliability of MP enumeration in wastewater and sludge samples as well as simpler sample matrices …”
Section: Introductionmentioning
confidence: 99%
“…Global attention on microplastics has increased because of their ubiquity in water, air, soil, and organisms. Knowledge of the sources, occurrences, behaviors, and health risks of microplastics is quite limited. Nevertheless, developing comprehensive health-based thresholds and regulatory guidelines for microplastics in water is impossible because of the limitations and complexity of determining their health effects. Writing in Environment & Health , Chowdhury et al reported a “Threshold Microplastics Concentration” (TMC) concept and framework . The TMC framework was used to identify microplastic concentrations that may result in the intake of regulated contaminants on/in microplastics at levels of human health concern and treatment targets for managing those potential risks …”
mentioning
confidence: 99%
“…Writing in Environment & Health , Chowdhury et al reported a “Threshold Microplastics Concentration” (TMC) concept and framework . The TMC framework was used to identify microplastic concentrations that may result in the intake of regulated contaminants on/in microplastics at levels of human health concern and treatment targets for managing those potential risks …”
mentioning
confidence: 99%
See 2 more Smart Citations